Drug-induced liver injury: Relation between the R ratio and histopathology - O.M. Ardila-Suárez; L. Oriz-Benjumea; A.A. Arteta; L.G. Guevara-Casallas (Revista de Gastroenterología de México (English Edition), 2023)
Introduction and aim: Drug-induced liver injury (DILI) is a diagnosis based on the ruling out of potential liver diseases and consolidated by establishing causality through the temporal relation between a potentially hepatotoxic substance and altered liver biochemistry. Incidence fluctuates greatly worldwide, with very few reports of causal agents of DILI in Colombia.A retrospective study on patients treated at the Centro de Estudios en Salud (CES), within the time frame of January 2015 and June 2020, was conducted to document the causal substances of DILI in patients with liver biopsy and to correlate the types of histologic patterns with the biochemical pattern of liver injury (R ratio). Results: Of the 254 adult patients with liver biopsy and no tumor etiology, 20 patients were identified as cases of DILI (7.87%). The two most frequently found causal substances were efavirenz, in three HIV-positive patients, and Moringa oleifera (moringa), in two patients. There was a statistically significant association between cholestatic patterns (p = 0.037) and mixed patterns (p = 0.031), in the comparison of the histopathologic categories and the R ratio. Conclusion: To the best of our knowledge, there are no reports on DILI secondary to Moringa oleifera (moringa). The R ratio could be a useful tool, in relation to the histologic pattern of injury, in cases of mixed and cholestatic patterns. Resumen: Introducción y objetivo: El daño hepático inducido por medicamentos (DILI, por sus siglas en inglés), es un diagnóstico basado en la exclusión de potenciales hepatopatías, y que se consolida, estableciendo la causalidad entre una sustancia potencialmente hepatotóxica y la alteración del perfil bioquímico hepático. La incidencia de este fenómeno fluctúa en un amplio rango a nivel mundial, con muy poca documentación de los agentes causantes de DILI en Colombia.Con el objetivo de documentar las sustancias causantes de DILI en pacientes con biopsia hepática y de relacionar los tipos de patrones histológicos con el perfil analítico de toxicidad (índice R), se realizó un análisis retrospectivo de los pacientes atendidos en la clínica CES (Centro de Estudios en Salud) entre enero de 2015 y junio de 2020. Resultados: De 254 pacientes adultos, con disponibilidad de biopsia hepática sin etiología tumoral, 20 pacientes fueron identificados como DILI (7.87%). Las dos sustancias más frecuentemente encontradas fueron efavirenz en tres pacientes HIV positivos, y en dos pacientes Moringa oleifera (Moringa). Se encontró asociación significativa entre los patrones colestásicos (p = 0.037) y mixtos (p = 0.031) en la comparación de las categorías histopatológicas y el índice R. Conclusión: En lo mejor de nuestro conocimiento, no hay reportes de casos de DILI secundarios a Moringa oleifera (Moringa). El índice R podría ser una herramienta útil de relación con el patrón histopatológico, para el caso de los patrones mixto y colestásico.